LONG TERM PROJECTION OF ELECTRICITY GENERATION SECTOR IN WEST PAPUA PROVINCE: LEAP MODEL APPLICATION - Etika Nur'Aini; Isra Nuur Darmawan; Mohammad Alfiza Rayesa (Master in Systems Engineering, 2020)
Electricity is one of the crucial infrastructures in economic development. The number of registered customers electricity increases every year based on data from the State Electricity Company (PLN) Manokwari branch office data. Electricity increase because it has become an essential part of everyday life. Therefore, in West Papua, it is necessary to fix this electricity problem where the most significant source is still from fossils. By looking at potential sources in West Papua that are more sustainable and renewable to meet public electricity demand in West Papua.In this study, LEAP software will simulate several scenarios, namely based on data from the RUPTL (Electricity Supply Business Plan) and further digging based on the potential literature in West Papua. There will be three scenarios; scenario 1 uses BAU (Business as Usual) as available in RUPTL. Scenario 2 uses BAU data and adds potential renewable energy. Scenario 3 is not using fossil energy but using renewable energy. The result is West Papua can be 100% electrified in 2025 if using scenario 2. The potential for renewable energy in West Papua is wind and sun. However, it does not rule out other sources, such as hydropower.